MATERNAL AND PERINATAL OUTCOMES IN PRETERM PREMATURE RUPTURE OF MEMBRANES (PPROM): A PROSPECTIVE OBSERVATIONAL ANALYSIS. - Nazaneen, Syed; Pankaj, Sangeeta; Kumari, Amrita (Student's Journal of Health Research Africa, 2024)
Background One of the main causes of preterm births and a major contributor to neonatal morbidity and death is preterm premature rupture of membranes, which is defined as membrane rupture before 37 weeks of gestation without the commencement of labor. This study aims to assess the maternal and perinatal outcomes linked to PPROM and to pinpoint important risk factors influencing these outcomes. Methods This prospective multicenter study included 80 pregnant women diagnosed with PPROM. The diagnosis was based on clinical history, sterile speculum examination, and confirmation via ultrasound. Participants, grouped by gestational age at PPROM onset (24–36 weeks), underwent conservative or active management based on gestational age and clinical condition. Maternal and neonatal outcomes were monitored, including infection rates, latency periods, neonatal APGAR scores, NICU admissions, and complications. Statistical analysis assessed associations between management approaches and outcomes. Results Of the 80 participants, 60% experienced maternal complications, with chorioamnionitis (35%) and postpartum hemorrhage (12.5%) being the most common. Neonatal complications included low APGAR scores in 23.8% of cases, NICU admissions in 62.5%, and a neonatal mortality rate of 7.5%. Conservative management in patients below 34 weeks led to prolonged latency but increased infection rates, while active management in cases above 34 weeks reduced maternal complications. Key predictors of adverse outcomes were gestational age at PPROM onset, maternal age, and presence of infection. Conclusion Gestational age and prompt infection control significantly influence PPROM outcomes. Conservative management is beneficial in extending gestational age but necessitates strict monitoring to prevent infections. Induction in cases above 34 weeks effectively minimizes maternal risks without compromising neonatal outcomes. Recommendations For cases <34 weeks, conservative management with vigilant infection monitoring is recommended, while for cases >34 weeks, induction may be beneficial. Further research is needed to optimize individualized treatment protocols based on gestational age and maternal-fetal conditions.